The mediating effect of MSMEs export performance between technological advancement capabilities and business performance - Hussain, Fawad; Saud, Mohammad Basir; Md Isa, Mohd Azwardi (2015)
The aim of this study is to empirically investigate the mediating impact of export performance (EP) between technological advancement capabilities (TAC) and business performance (BP) of Malaysian manufacturing MSME’s.Firm’s technological advancement resources are hypothesized as a platform to enhance both exports and business performance of manufacturing MSMEs in Malaysia.This study is twofold, primary it has investigated that technological advancement capabilities helps to appreciates main performance measures noted in terms of export performance and Secondly it investigates that how efficiently and effectively technological advancement capabilities can contributes in overall Malaysian MSME’s business performance.Smart PLS-3 statistical software is used to know the association between technological advancement capabilities, MSME’s export performance and business performance.In this study the data was composed from Malaysian manufacturing MSME’s in east coast industrial zones known as manufacturing hub of MSMEs.Seven Hundred and Fifty (750) questionnaires were distributed but only 148 usable questionnaires are returned.The finding of this study indicated that technological advancement capabilities helps to strengthen the export in term of time and cost efficient and it plays a significant role in appreciating their business performance.This study is helpful for small and medium enterprises owners who intent to expand their business overseas and though smart technological advancement resources they can achieve their business competitiveness and excellence both at local and international markets.